The Impact of Partner Reading and Text-based Discussion on Iraqi EFL Students’ Literary Skills Development - Bani Madhi, Majid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study verifies whether the partner reading and text-based discussion has any impact on developing Iraqi EFL students’ literary skills. The study focuses on comprehension, interpretation, and critical analysis skills . The study adopted a mixed-methods quasi-experimental design applied to 120 high school students. The study experimental groups include partner reading, text-based discussion, and their combination, and a control group taught by traditional instruction. Quantitative findings revealed the superiority of the experimental groups in all targeted literary skills. Remarkably, the combined approach attained the greatest improvements. Moreover, qualitative findings revealed that the experimental groups showed less language anxiety and more engagement. Furthermore , they suggested the importance of role-based management and teacher training for successful implementation in limited-resource classrooms. L1 use and large class sizes were major issues in implementing partner reading and text-based discussion instruction . The study highlights the importance of cooperative and collaborative strategies in developing literary skill acquisition in similar educational contexts and this suggests modernizing EFL pedagogy in Iraq. DOI: https://doi.org/10.54633/2333-024-057-022